2012
DOI: 10.1111/j.1465-3362.2012.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion and drug policy in Australia: Engaging the ‘affected community’

Abstract: These findings provide a springboard for further investigation of the attitudes of people who use illicit drugs towards drug policy in Australia, and challenge us to conceptualise how the opinions of this community should be solicited, heard and balanced in drug policy processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 18 publications
5
38
0
Order By: Relevance
“…Although recent data have shown that there continues to be a perception of substantial risk associated with marijuana use in the general population [11], other data indicate that risk perception is significantly lower in individuals with substance use disorders [12]. This finding supports previous work highlighting the importance of engaging the 'affected community', who may have different perspectives from the general population [13].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although recent data have shown that there continues to be a perception of substantial risk associated with marijuana use in the general population [11], other data indicate that risk perception is significantly lower in individuals with substance use disorders [12]. This finding supports previous work highlighting the importance of engaging the 'affected community', who may have different perspectives from the general population [13].…”
Section: Introductionsupporting
confidence: 76%
“…To this end, we employed the use of qualitative methodology, allowing participants to provide open-ended narratives and to facilitate the exploration of underlying meanings and motivations attributed to specific perspectives [17]. Secondly, we purposively sampled individuals with substance use disorders in recognition of empirical and theoretical arguments supporting the relevance of obtaining the perspective of the 'affected community' [13]. Our study represents an early, yet significant description of these perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…While public opinion is considered an important factor in drug policy development (Matthew-Simmons, Love, & Ritter, 2008), little research has explored what people who use drugs themselves think about drug policy. A small amount of research has recently examined what people who inject drugs think about drug policy, revealing heterogeneity of opinion about a range of drug policy issues and nuanced views on the legal status of different drug types (Darke & Torok, 2013;Lancaster, Ritter, & Stafford, 2013). Lancaster et al (2013) found that when compared with the opinions of the Australian general population, people who inject drugs expressed substantially higher levels of support for harm reduction measures and legalisation of the personal use of drugs, but substantially less support for increased penalties for the sale and supply of illicit drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Clients suggested that the measures identified required them to 'become superhuman', and did not capture sufficiently the complexity of their embodied experiences or circumstances. I suggest that this disjuncture between how clients and clinicians view 'recovery' not only re-emphasizes the value of including the voices of people who use drugs in policy processes and treatment systems [10][11][12], but also raises other questions which require critical consideration.First, it might be necessary to interrogate the assumptions and conceptual premises which lodge within the concept of 'recovery' [13]. The measures put forward by treatment providers in Neale's study [7] accord with McKay's [1] concerns and other definitions of 'recovery' developed by experts internationally [14,15], by focusing not only upon reduced drug use and improved health, but also upon notions of citizenship, roles and responsibilities.…”
mentioning
confidence: 99%
“…Clients suggested that the measures identified required them to 'become superhuman', and did not capture sufficiently the complexity of their embodied experiences or circumstances. I suggest that this disjuncture between how clients and clinicians view 'recovery' not only re-emphasizes the value of including the voices of people who use drugs in policy processes and treatment systems [10][11][12], but also raises other questions which require critical consideration.…”
mentioning
confidence: 99%